The Development of Corporate Financing Law: Empirical Practices of Business Financing in the "PaDi UMKM" Marketplace - Shafa Dinda Putri; Tarsisius Murwadji; Etty Mulyati (Khazanah Hukum)
Micro Small Medium Enterprises (MSMEs) are the largest segment of national economic actors that can continue to grow. Still, in practice, MSMEs are difficult to develop because several obstacles are faced, especially in the digital world, which is difficult to get financing because of the unfulfilled collateral requirements. In its development, corporate financing also uses information technology media. This research aims to analyze juridical reviews of Corporate Finance Law in digital platforms, business financing practices on MSMEs Digital Market (PaDi) Marketplace in MSMEs development efforts, and invoice financing as collateral development in MSMEs company financing. The research methods used are normative juridical with analytical descriptive research specifications. The results of this study show: (1) corporate financing has been regulated in several laws and regulations and related to its development in digital platforms is implied to be regulated through Financial Services Authority Regulation Number 13/POJK.02/2018; (2) MSMEs Digital Market (PaDi) Marketplace acts as a facilitator of buying and selling as well as providing finance; and (3) the new securities theory of Performance Securities is realized through invoice financing as finance without collateral.